Analysis of Energy Transmission and Deformation Characteristics of Coal-Rock Combined Bodies. (28th June 2022) - Tuo, Wang; Fuzhou, Qi; Jucai, Chang
Abstract : A coal-rock system is a common combination form in coal mines. In order to explore the energy interchange law of a coal-rock combined body and the interaction relationship between the two bodies, loading tests of coal-rock combined bodies with different height ratios were carried out. The loading path of rock in coal-rock combined bodies was demonstrated by means of a single loading and unloading test of the same-sized rock sample. Furthermore, a method to calculate rock energy was proposed based on the area of the loading and unloading curve. The experimental results show that the greater the surrounding rock pressure is, the smaller increase rate of lateral and volumetric strain in the postpeak stage will be when the same height ratio is present. An increase in the surrounding rock pressure causes an increase in the total strain energy density of small-sized rock samples. However, the total strain energy density is always greater than the elastic strain energy density. And the elastic and dissipated strain energy densities also increase, along with the energy dissipation with unloading. When the proportion of coal bodies increases, the energy accumulation also shows an increasing trend. When the height of the coal is greater than half the height of the complete specimen, the coal energy proportion is greater than 60%. After reaching the yield load, the energy in the coal body is dissipated in forms such as plastic deformation, internal damage, block friction, radiation energy, and kinetic energy. Therefore, the energy released is, in part, reflected in the rock body.